Dynamic nonlinear control strategies for resilient heterogeneous vehicle platooning and handling Byzantine attacks in communication networks - Ammar Alsinai; José Roberto Castilho Piqueira; Waqar Ul Hassan; Azmat Ullah Khan Niazi; Farida Safder (Heliyon)
This paper addresses the challenges of maintaining stability in heterogeneous vehicle platooning under the influence of communication disruptions caused by Byzantine attacks within a leader-follower framework. To enhance resilience, we propose a nonlinear control strategy tailored for a third-order heterogeneous dynamic model, integrating leader-follower interconnections with adaptable control gains. Utilizing a constant time headway spacing policy with gap adjustments, we derive control gains that secure internal platoon stability. A Lyapunov-based stability approach is employed to mitigate the destabilizing effects of Byzantine attacks, ensuring robust performance even in adverse conditions. Numerical simulations validate the controller's effectiveness, showing rapid convergence to stable platoon behavior within 10 seconds and maintaining a tracking error below 10 percent, despite simulated attacks. These results demonstrate the practical feasibility of the proposed controller in ensuring stability and resilience in real-world platooning scenarios where communication integrity is compromised.